Alteration of Myeloid-Derived Suppressor Cells, Chronic Inflammatory Cytokines, and Exosomal miRNA Contribute to the Peritoneal Immune Disorder of Patients With Endometriosis. (August 2019) - Chen, Ya; Wang, Kangxia; Xu, Yuping; Guo, Peipei; Hong, Baoli; Cao, Yunxia; Wei, Zhaolian; Xue, Rufeng; Wang, Chao; Jiang, Huanhuan
Immunologic disorder has been reported to promote the progression of endometriosis (EMT). It has been known that myeloid-derived suppressor cells (MDSCs) drive the progression of many types of diseases. Few studies have shown the relation between MDSCs and EMT. To test whether MDSCs play a role in the progression of EMT, we defined MDSCs, cytokines, and the exosomal microRNA (miRNA) profile in peritoneal fluid (PF) from EMT patients. Characteristics of MDSCs, regulatory T cells (Tregs) and effector T cells were quantified by flow cytometry. Peritoneal fluid monocyte chemoattractant protein (MCP) 1/3, hepatocyte growth factor (HGF), chemokine (C-X-C motif) ligand (CXCL) 1/2, and 13 other cytokines were performed by enzyme-linked immunosorbent assay kit. Exosomal miRNA sequencing was prepared from PF of 3 women with early-stage EMT, 3 women with advanced stage EMT, and 3 women from control group. Our results showed that accumulations of monocytic MDSCs (Mo-MDSCs) and Tregs were detected in advanced patients with EMT. Patients with EMT displayed a significantly higher production of PF CXCL1, CXCL2, MCP-1, MCP-3, and HGF as compared to those from controls. MicroRNA sequencing showed 13 exosomal miRNAs (miRNA-1908, -130b, -451a, -486-5p, -4488, -432, -342, -425, -505, -6508, -145, -365a, and -365b) which are involved in immune alteration and cell proliferation and were differentially expressed in patients with EMT (fold-change ± 2.0). In conclusion, our study revealed that Mo-MDSCs, inflammatory cytokines, and exosomal miRNA seem to be involved in the progression of EMT; however, the relation between Mo-MDSCs, cytokines, and miRNA needs further research.